The influence of Leader’s refusal to Internet-based communication on communication satisfaction - Bedoya, Ever (Open Science Journal, 2020)
New organizational investments in ICT tools have led companies to increase the use of Internet-based communication channels, nevertheless, some leaders still refuse to use them; hence, this study tests if the leader's refusal to communicate via Internet -based channels with employees has no influence on communication satisfaction; the sample consisted of 103 participants from Colombian organizations; a questionnaire and interviews were administered; subsequently, data was analyzed by using SPSS and Atlas Ti tools. The results concluded that the absence of internet-based communication channels in the organization does not affect communication satisfaction, and it was also observed that employees are willing to use traditional communication channels instead. The findings are important as a input for scholars who want to deepen the understanding of Internet-based communication channels and their effect on satisfaction communication; similarly, the results may assist organizations in redesigning organizational communication policies while they adapt to virtual work during the Covid19 outbreak.